Reaction of selected winter wheat cultivars to an increase in the intensity of cultivation technology - Jańczak-Pieniążek, Marta; Buczek, Jan; Bobrecka-Jamro, Dorota (Polish Journal of Agronomy, 2020)
The field experiment with winter wheat was conducted in the years 2016–2019 at the Experimental Stations of Cultivar Assessment in Przecław. The experimental factors were: I – ag-ricultural technology with different intensity level (medium-in-tensity A1 and high-intensity A2), II – cultivar of winter wheat (‘Hondia’, ‘RGT Kilimanjaro’, ‘Patras’, ‘Pokusa’). Wheat pro-duction technologies were differed in the use of plant protection products, doses of mineral fertilization and additional use of foli-ar fertilization and growth regulator in high-intensity technology. The use of technology with a higher intensity level significantly increased the value of yield-forming parameters, grain yield and grain quality parameters, but did not differentiate the fiber and ash content in the grain. ‘RGT Kilimanjaro’ was distinguished from the other cultivars by the highest level of grain yield, the most favorable values of grain quality parameters (protein, glu-ten content, test weight, sedimentation index) and the lowest fat and ash content. Weather conditions prevailing in the 2018/2019 season, characterized by a low rainfall sum and high temperature during the formation of kernels, increased the value of grain qual-ity and chemical parameters, but caused a decrease in grain yield.